2019
DOI: 10.22159/ijpps.2019v11i3.30452
|View full text |Cite
|
Sign up to set email alerts
|

A Review on the Pharmacological and Traditional Properties of Mimosa Pudica

Abstract: Consumption of fruits and vegetables fight against oxidative damage by inhibiting or reducing free radicals and reactive oxygen species. Mimosa pudica is a perennial herb and belongs to the family Fabaceae. Epidemiological studies have shown that M. pudica contains metabolites such as phenols and flavonoid compounds which possess pharmacological properties such as antidiabetic, antimicrobial, antiulcer, antidepressants and anti-inflammatory. Ecological studies have shown that M. pudica grows in all types of so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 24 publications
0
1
0
Order By: Relevance
“…Mimosa pudica, commonly known as Lajjalu in Ayurveda, has established itself as a prominent botanical resource with versatile therapeutic applications. Within traditional medicine, it serves as a valued antidepressant and anti-asthmatic agent, playing a role in the treatment of a diverse range of ailments Hassan, et al, 2019. This utilization is rooted in Ayurvedic practices, where the plant has been acknowledged for its potential to address psychological and respiratory health concerns.…”
Section: Related Workmentioning
confidence: 99%
“…Mimosa pudica, commonly known as Lajjalu in Ayurveda, has established itself as a prominent botanical resource with versatile therapeutic applications. Within traditional medicine, it serves as a valued antidepressant and anti-asthmatic agent, playing a role in the treatment of a diverse range of ailments Hassan, et al, 2019. This utilization is rooted in Ayurvedic practices, where the plant has been acknowledged for its potential to address psychological and respiratory health concerns.…”
Section: Related Workmentioning
confidence: 99%
“…Phytochemical studies on Mimosa pudica have revealed the presence of alkaloids, fatty acids, non-protein amino acid 19,20 , flavonoids, C-glycosides, sterols, terpenoids, and…”
Section: Figure 1: Mimosa Pudica Plantmentioning
confidence: 99%